1994
DOI: 10.1111/j.1440-1827.1994.tb01687.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasive ductal carcinoma with a predominant intraductal component arising in a fibroadenoma of the breast

Abstract: A rare case of invasive ductal carcinoma with a predominant intraductal component arising within a fibroadenoma of the breast in a 42 year old Japanese female was investigated by light microscopy. The patient, who had a well-defined, rubbery breast tumor measuring 2.0 x 3.0 cm, had undergone a tumorectomy 21 months after she noticed the tumor. Histologically, the fundamental architecture of the tumor showed an intracanalicular-type of fibroadenoma, but extensive proliferation of atypical cells was noticed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…The histological diagnosis of carcinoma arising within a fibroadenoma has been based on the criterion that the carcinoma cells were limited to a well-defined fibroadenoma or only focally extended into adjacent stroma or ducts. 11 The prevalence of carcinoma within fibroadenomas in a screened population was reported to be 0.02% by Deschenes et al 18 Similarly, Buzanowski-Konakry et al 19 identified five cases in a review of 4000 fibroadenomas examined over a 43-year period. 20 The rarity of carcinoma within fibroadenomas is reflected by the relatively few series 2,19-21 and case reports, and the behavior of these tumors is not well established.…”
Section: Discussionmentioning
confidence: 94%
“…The histological diagnosis of carcinoma arising within a fibroadenoma has been based on the criterion that the carcinoma cells were limited to a well-defined fibroadenoma or only focally extended into adjacent stroma or ducts. 11 The prevalence of carcinoma within fibroadenomas in a screened population was reported to be 0.02% by Deschenes et al 18 Similarly, Buzanowski-Konakry et al 19 identified five cases in a review of 4000 fibroadenomas examined over a 43-year period. 20 The rarity of carcinoma within fibroadenomas is reflected by the relatively few series 2,19-21 and case reports, and the behavior of these tumors is not well established.…”
Section: Discussionmentioning
confidence: 94%
“…Diaz et al3 followed general criteria established for the recognition of carcinoma of the breast. Some investigators have defined carcinoma arising within fibroadenoma as having carcinoma cells which are limited to a well-defined fibroadenoma or which only focally extend into the adjacent stroma or ducts 9. In the present case, foci of intraductal carcinoma were detected in adjacent breast tissue of resection margins and DCIS was predominantly involved in fibroadenoma.…”
Section: Discussionmentioning
confidence: 48%
“…Clinically, for breast tumors that are diagnosed as fibroadenomas, many cases are determined on follow-up observations. Carcinoma arising on a fibroadenoma is rare [3,4,5]; the frequency has been reported to be equal to or less than 0.5% [6]. In the current case, the mammographic findings showed coarse calcifications, a hallmark of benignity; however, the mass had an irregular and indistinct margin, which was an atypical finding for fibroadenoma, thus suggesting a malignancy [7].…”
Section: Discussionmentioning
confidence: 58%